Beyond the Benefits of Interdisciplinary Meetings for Knowledge Firms: A Double-Edged Organisational Tool - Proisy,Tatiana; Gosselin,Francesca (2018)
Cross-functional teams and meetings are recurrent structuring tools in contemporary knowledge organisations. They are recommended as solutions to enhance innovation and creativity. Current research gathers a myriad of reference to the benefits of such tools, but studies of their potential negative effects remain limited. This paper is specifically concerned with the effect of interdisciplinary team meetings on knowledge workers in the context of knowledge-intensive firms. The aim of this research is therefore to provide insights in management studies for modern knowledge-based businesses. Our contribution is to enrich the academic fields of interdisciplinary meetings and identity work in knowledge firms. This study qualitatively explored interactions of knowledge workers within organisational meetings and the psychological impact these interactions may have. Our fieldwork included semi-structured interviews and observations of a recurrent meeting within a high-tech start-up. We paid particular attention to subjective interpretations and perceptions of knowledge workers in the context of an interdisciplinary meeting. Our results show that there is a close relationship between the modern concept of alienation and the idea of identity struggle. We suggest for further research to focus on such linkages and explore them in different contexts.